Effect of a Rho Kinase Inhibitor on Cognitive Impairment Induced by Chronic Cerebral Hypoperfusion in Rats - Zhang, Q.; Zhang, J. -J.; Han, Zh. -M. (Нейрофизиология, 2015)
We examined the efficacy of a Rho kinase inhibitor, Fasudil, on cognitive impairment induced by chronic cerebral hypoperfusion in rats. Thirty-two male adult Sprague-Dawley rats were randomly divided into three groups; treated (T), control (C), and sham-operated (Sh); severe stenosis of the carotid arteries was modeled in the former two groups. During two weeks, 8.35 mg/kg Fasudil and physiological saline were i.p. applied twice per day in the T and C groups, respectively. The Morris water maze test was performed in each group to detect changes in the cognitive function and to observe pathological shifts in hippocampal morphology in rats after eight weeks. The mean escape latency was distinctly shorter (P < 0.01), and the percentage of swimming distance within the platform quadrant was significantly greater (P < 0.01) in the T group, compared to those in the C group at the corresponding time points. The rate of carotid artery stenosis in rats demonstrated no statistical difference between the T and C groups (P > 0.05). Fasudil injections effectively normalized hippocampal pathomorphology in the T group. Thus, the Rho kinase inhibitor obviously ameliorated cognitive impairment induced by chronic cerebral hypoperfusion in rats.